Efektivitas Model Role Playing dalam Pembelajaran Pementasan Drama Siswa Kelas XI SMA Negeri 3 Soppeng - Fitriansal, Fitriansal (Nuances of Indonesian Language, 2024)
This research aims to: (1) Assess the competency of expressing dialogue between characters in drama performances for class XI students at SMAN 3 Soppeng by applying the role playing method in learning; (2) Testing the effectiveness of the role playing method in learning to express dialogue between characters in drama performances for class XI students at SMAN 3 Soppeng. The design used is an experimental research design (true experimental) with descriptive statistical data analysis techniques and inferential statistics. The population in this study were all class XI students of SMA Negeri 1 Donri-Donri, Soppeng Regency. The sample for this research was 134 students. Sampling was carried out by drawing lots for the classes that would be used as research samples. In this research, two classes were used as samples, namely classes XI IPA 1 and XI IPA 3. The technique used in collecting data was the test technique. The results of the research show that (1) The learning competency for drama performances of class XI SMAN 3 Soppeng using the role playing method is categorized as high with an average of 84.2 so the score obtained by students reaches the specified criteria, namely reaching 90%; (2) The role playing method is effectively applied in class XI SMAN 3 Soppeng with a value of tcount > ttable or 4, 727 > 2.09 at a significance level of 0.05. Based on the results of this research, suggestions are made: (1) Teachers should always apply the role playing method in teaching drama performances for class XI students at SMAN 3 Soppeng, especially in learning speaking aspects; (2) to improve learning, researchers should prioritize the role playing method because this method is effective in increasing students' abilities, motivation and love of learning; (3) It is hoped that future researchers in developing learning methods will continue to carry out research trials on role playing methods in all aspects of Indonesian language learning, even in other subjects.